Revolution 4.0 as a Factor of Change in the Labour Market - Giza, Wojciech; Sztokfisz, Barbara (Journal of Public Governance, 2021)
Objectives: The aim of the deliberations is to show how the exogenous factors, in this case the subsequent Industrial Revolutions, affected the structural changes of the labour market and how they were perceived by the economists.Research Design & Methods: The research area is limited to the theory that explains the functions of the labour market in the historical perspective. The study is a theoretical study that combines the elements of analysis in the field of economic history and the development of economic thought. The justification of the presented theses was made using the induction method and the comparative method, both of which enable the presentation of the labour market evolution process in a relatively long-time horizon.Findings: The structure of the study reflects the changes that have taken place in the economic theory under the influence of the Industrial Revolutions. The last of them, the Revolution 4.0, is a reference point to form the key questions regarding the automation and redistribution of income that the contemporary labour market researchers are concerned with.Implications / Recommendations: In the theoretical dimension, the attention was drawn to the usefulness of the comparative analysis method for understanding the profound changes in the labour market. The practical aspect of the research is to identify the potential threats that arose as a consequence of the Revolution 4.0. Understanding them makes it possible to take action in the field of social, economic, and educational policies that aim at reducing social tensions resulting from dynamic changes taking place in the labour market.Contribution / Value Added: The technological progress is most often treated as a key factor that affects the supply side of the economy. It enables an increase of the productive potential of highly developed societies. The presented considerations reveal the analogies that arise in connection with the functioning of the labour market in the context of subsequent technological revolutions. Particular attention was paid to the influence of technological progress on the demand side of the economy and the consequences related to the distribution of income. The article is an attempt to supplement the reflection on the impact of the latest advancements in information technology with the context of historical changes that have taken place in the labour market.Article classification: theoretical article, conceptual articleJEL classification: O31, O33, B30, J31